(untitled) (CAHIERS MAGELLANES-NS, 2024)
The article presents the results of studying the growth, formation of leaf surface, productivity, and marketable yield of various ultra-early, early, and mid-early potato varieties with a double-cropping crop, that is, summer planting with freshly harvested tubers. It was revealed that the studied varieties differ significantly in the germination of tubers, the formation of top stems, and leaf surfaces, and in marketable yield. The highest field germination of tubers (95.2-98.7%), stem formation (2.9-3.8 pcs.), leaf surface (33.6-39.9 thousand m2 per 1 ha), photosynthetic potential on plantings (2590.0-3351.6 thousand m2), powerful tops and root systems with intensively accumulating yield, as well as the largest marketable yield (29.1-34.3 t/ha) were obtained from the varieties Latona, Binella, Karatop, Ultraeshim, Arizona, American, Yangishahar, Evolution, Pikasso, Sylvana, Saviola. At the same time, the yield increase was 2.6-8.7 t/ha compared to standard varieties.